Blurred Lines: Reconsidering the Concept of 'Diversion' in Youth Justice Systems in Australia. (August 2014) - Richards, Kelly
This article revisits 'diversion' in the context of youth justice in Australia. Although 'diversion' is omnipresent in youth justice, it is rarely subject to critical examination. This article raises four interrelated questions: what young people are to be 'diverted' from and to ; whether young people are to be 'diverted' from the criminal justice system or from offending ; whether young people are to be 'diverted' from criminal justice processes or outcomes ; and whether 'diversion' should be considered distinct from crime prevention and early intervention. The article concludes that the confusion about youth 'diversion' may foster individualized interventions in young people's lives.